TINGKAT KETERAMPILAN SHOOTING FUTSAL PADA PESERTA DIDIK EKSTRAKURIKULER SMP NEGERI 1 MARTAPURA - Nurramadhan, Raihan; Ramadhan Arifin; M. Mulhim (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
TThe field is short and mistakes are almost impossible in futsal because of the game's high speed and intensity. Using a sample population of SMP Negeri 1 Martapura extracurricular students, this research is a quantitative descriptive study employing a purposive sampling approach. According to the futsal shooting results of SMP Negeri 1 Martapura extracurricular students, the category of